Խոսքի մշակույթի հիմնաբաղադրատարրերը և դրանց դերը նորմավորման գործընթացում - Զ. Խ. Աղաջանյան (ՀՀ ԳԱԱ հրատ.)
Предметом изучения культуры речи является речь. Во все времена человек старался и старается усовершенствовать свою речь. Однако до сих пор не уточнено, как она соотносится с языком и мышлением, объектом изучения какой научной дисциплины является? The subject of studying the culture of speech is the speech. At all times a man has tried and tries to improve his speech. Nevertheless, until now it is not specified what speech is, in what relations it is with language and thinking, which of the linguistic-philological problems does it study.
Keywords: Philology; Linguistics; Language and Literature